Legal Implication of Black Campaigns on The Social Media in The General Election Process - Nyndya Fatmawati Octarina; Hardianto Djanggih (Jurnal Dinamika Hukum, 2019)
This study aims to examine the problems of black campaign on social media in the process of Regional Leader elections. The method used was a normative legal research with a qualitative approach to analyze the phenomena among the objects of the study with a conceptual and a case approach. The result indicates that the legal implication of the black campaign on the conduct of Regional Leader elections is that black campaign is not an option in politics. In addition to comprising detrimental things and violating the norm, black campaign also leads to poor political education for the society and can harm both the objects that are imposed and the black campaigners as this matter can be subject to criminal sanctions as stipulated in the Law of Election and Electronic Information and Transactions. For further research, there is a need for serious handling through criminal law and other facilities so that the implementation of elections to the regions as the actualization of democracy in Indonesia results in more valuable quality so as to create trustworthy Regional LeadersKeywords: Regional Head Election; Black Campaign; Social Media.